Crystallization and preliminary X‐ray analysis of the ATPase domain of the σ54‐dependent transcription activator NtrC1 from Aquifex aeolicus bound to the ATP analog ADP–BeFx. Issue 12 (1st December 2013) - Sysoeva, Tatyana A.; Yennawar, Neela; Allaire, Marc; Nixon, B. Tracy
<x xml:space="preserve">Abstract</x> One way that bacteria regulate the transcription of specific genes to adapt to environmental challenges is to use different σ factors that direct the RNA polymerase holoenzyme to distinct promoters. Unlike σ70 RNA polymerase (RNAP), σ54 RNAP is unable to initiate transcription without an activator: enhancer‐binding protein (EBP). All EBPs contain one ATPase domain that belongs to the family of ATPases associated with various cellular activities (AAA+ ATPases). AAA+ ATPases use the energy of ATP hydrolysis to remodel different target macromolecules to perform distinct functions. These mechanochemical enzymes are known to form ring‐shaped oligomers whose conformations strongly depend upon nucleotide status. Here, the crystallization of the AAA+ ATPase domain of an EBP from Aquifex aeolicus, NtrC1, in the presence of the non‐hydrolyzable ATP analog ADP–BeFx is reported. X‐ray diffraction data were collected from two crystals from two different protein fractions of the NtrC1 ATPase domain. Previously, this domain was co‐crystallized with ADP and ATP, but the latter crystals were grown from the Walker B substitution variant E239A. Therefore, the new data sets are the first for a wild‐type EBP ATPase domain co‐crystallized with an ATP analog and they reveal a new crystal form. The resulting structure(s) will shed light on the mechanism of EBP‐type transcription activators.